Upaya Meningkatkan Kreativitas Anak Usia 5-6 Tahun melalui Media Losse Part di RA Masyithoh V - Novitasari, Siti Ika; Dirgayunita, Aries (Asian Journal of Early Childhood and Elementary Education, 2024)
This study aims to improve children's creative abilities in producing their own work, creativity in children's thinking abilities in solving problems, and creativity in processing words in telling their ideas. This research uses the CAR method with three cycles, each cycle consisting of 2 meeting. The subjects of this study were children aged 5-6 years at RA Masyitoh V, Probolinggo City, with the problem of the lack of creativity in children. The average result in cycle 1 with the developing category is 18% according to expectations. The results in cycle 2 showed an increase in the average category Developing According to Expectations (BSH) 51%, Developing Very Well (BSB) 42% and the average increase in stage 3, namely the category Developing very well as much as 76%. The conclusion from this study is that the use of loss part media is quite effective in improving the abilities of children aged 5-6 years at RA Masyitoh V.